Performance aside… the organizational and director level determinants of boards’ compensation - Osiichuk, Dmytro (Publishing House of Wroclaw University of Economics and Business, 2021)
Relying on a cross-country panel database, the paper explores the non-performance-related factors affecting the remuneration of supervisory boards. The author demonstrated that entrenched boards benefiting from statutory limitations on director removal and limited director liability receive a higher compensation. In contrast to previous studies, it was shown that the CEO’s power over the board positively contributes to the directors’ remuneration suggesting that the lack of checks on executives may undermine the board’s ability to monitor the management. Overall, a higher workload, board diligence, independence, expertise and experience are shown to increase directors’ remuneration. However, the rewards for advanced tenure and supermajority-backed independence vanish in the tails of distributions of the respective variables. Those boards with the majority of directors possessing board-specific skills are seen to receive lower compensation possibly due to the higher substitutability of board members. Generally, the study proved that there is a certain saturation point when it comes to board independence, skills, and tenure. The use of executive retention and compensation- enhancing tools are seen to increase board compensation while simultaneously contributing to the widening in-house wage disparities
Argumenta Oeconomica, 2021, Nr 1 (46), s. 99-129